Delayed diagnosis of thoracic spine tuberculosis: a learning objective in primary care - Sunwar, Sabit; Saiyed, Abrar A. (International Journal of Clinical Trials, 2025)
Spinal tuberculosis (TB) constitutes 2% of all TB cases and is a common of all extrapulmonary TB. Despite high prevalence of TB worldwide, it is still sub-optimally controlled owing to the factors like poverty, rising human immuno-deficiency virus (HIV) infection and other chronic illnesses, drug misuse, population surge in developing countries and global migration. This case report presents a 38-year-old man who presented with recurrent chronic thoracic back pain. Further investigation in his third visit revealed a compression fracture of T7-8 vertebrae, with a pathologic fracture with spondylitis, epidural abscess and spinal cord compression suggestive of an infectious process, with tuberculosis being the primary differential diagnosis. We present our case to highlight the importance of a meticulous history taking and examination at first presentation and how cases of spinal TB should not be overlooked.